Coronavirus: an overview of Brazil’s international scientific collaboration throughout history - Rosane Abdala Lins (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2021)
The worldwide research effort on covid-19 is reflected in the increase in scientific publications. In order to investigate and describe Brazil’s international scientific collaborations on the topic, we performed a bibliometric analysis using the Scopus database as our data source, with a search strategy that included terms related to the virus and the disease. For the period ranging from 1989 to 2020, 3,255 publications were retrieved, 1,310 of which were international scientific collaborations, which were classified in terms of nationality, institutional affiliation, the journals in which they were published and their disciplines. The co-authored publications on covid-19 involved 148 countries, 104 of which are new partners. Over the period analyzed, new areas of knowledge were incorporated into the discussion on the subject.